Interseismic coupling, seismic potential, and earthquake recurrence on the southern front of the Eastern Alps (NE Italy). Issue 5 (23rd May 2014) - Cheloni, D.; D'Agostino, N.; Selvaggi, G.
Abstract Here we use continuous GPS observations to document the geodetic strain accumulation across the South‐Eastern Alps (NE Italy). We estimate the interseismic coupling on the intracontinental collision thrust fault and discuss the seismic potential and earthquake recurrence. We invert the GPS velocities using the back slip approach to simultaneously estimate the relative angular velocity and the degree of interseismic coupling on the thrust fault that separates the Eastern Alps and the Venetian‐Friulian plain. Comparison between the rigid rotation predicted motion and the shortening observed across the area indicates that the South‐Eastern Alpine thrust front absorbs about 70% of the total convergence between the Adria and Eurasia plates. The coupling is computed on a north dipping fault following the continuous external seismogenic thrust front of the South‐Eastern Alps. The modeled thrust fault is currently locked from the surface to a depth of ≈10 km. The transition zone between locked and creeping portions of the fault roughly corresponds with the belt of microseismicity parallel and to the north of the mountain front. The estimated moment deficit rate is 1.3 ± 0.4 × 1017 Nm/yr. The comparison between the estimated moment deficit and that released historically by the earthquakes suggests that to account for the moment deficit the following two factors or their combination should be considered: (1) a significant part of the observed interseismic coupling is released aseismically and (2) infrequent "large" events with long return period (> 1000 years) and with magnitudes larger than the value assigned to the largest historical events (Mw≈ 6.7).